RESTRUKTURISASI MAJELIS PERMUSYAWARATAN RAKYAT SESUDAH AMANDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Alsidik Syahputra; Dodi Haryono; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Institution of the People's Consultative Assembly was referred to as the supreme perpetrators of popular sovereignty even in Article 1 (2) of the Constitution of 1945 before the change formulated by the sentence: "The sovereignty of the people's hands and performed entirely by the Assembly". Now, the provisions of Article 1 (2) altered its formulation into "the hands of the people's sovereignty and implemented in accordance with the Constitution". The purpose of this study was, first, to know clearly the position of the Assembly before and after the amendment of the Constitution of the Republic of Indonesia Year 1945. Second, to determine the urgency of institutional restructuring of the People's Consultative Assembly in the state system of Indonesia. Third, to determine the implications of changes in the position of the Assembly on the principle of popular sovereignty. From this research, there are three things that can be concluded, first, notch the Assembly before the amendment is the holder of the rule or the highest power. The position of the Assembly after the amendment is no longer as the highest state institution, the position of all state agencies are aligned as state institutions. Secondly, in connection with the checks and balances it is also proposed the idea of changes to the parliamentary system of the supremacy of the Assembly became the parliamentary bicameral system (two rooms) are interwoven in a relationship of checks and balances. Third, the amendment to article 1, paragraph (2) and Article 2, paragraph (1) implicated in, reposition the role of the Assembly of the highest state institutions (the supreme body) into the joint between the House of Representatives and the Regional Representatives Council. Suggestions writer, First, people's Consultative Assembly session which is a joint forum of the Board of Representatives and Regional Representative Council does not need to be permanent so that more precise leadership of the Assembly ad hoc course, do not need a separate secretariat and leadership. Second, Reinforce a legislative system adopted whether unicameral system (one room) that the House of Representatives and the Regional Representatives Council remove institution or adopts a bicameral (two rooms), namely the House of Representatives and Regional Representative Council with the consequences of having a very strong position. Third, Indonesia should be able to follow the United States, on the relationship between the House of Representatives (DPR) and the senate in congress (parliament) who put both in a balanced legislative function and can perform mutual checks and balances.Keywords: Restructuring - MPR - amendment – Constitution of 1945